Negative electrode material and secondary battery

By using characteristic silicon carbon materials and carbon-based material cladding in lithium-ion batteries, the volume expansion and cycling performance problems of silicon negative electrode materials are solved, and efficient lithium-ion battery performance improvement is achieved.

CN119275266APending Publication Date: 2025-01-07BTR NEW MATERIAL GRP CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411377512.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Silicon negative electrode materials are difficult to meet the needs of commercial applications due to large volume expansion, poor circulation performance and poor conductivity in lithium-ion batteries.

Method used

Using a negative electrode material including silicon-carbon materials, Raman spectral testing ensures that the characteristic peak intensity relationship is within a specific range, combining the carbon-based material cladding layer and the reasonably designed silicon-based material particle structure to form a conductive network to suppress volume expansion and increase Mechanical strength.

Benefits of technology

Lithium-ion batteries with high capacity, high first efficiency, long cycle life and excellent rate performance have been achieved, reducing the expansion rate and side reaction of the negative electrode material and improving electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275266A_ABST
    Figure CN119275266A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a secondary battery. The negative electrode material comprises a silicon-carbon material, the silicon-carbon material comprises a silicon-based material and a carbon-based material, and at least part of the carbon-based material is distributed in the silicon-based material; a Raman spectrum is adopted to test the negative electrode material, the negative electrode material has a first characteristic peak at 515 + / -10 cm <-1 >, and the peak intensity of the first characteristic peak is M1; a second characteristic peak exists at 305 + / -10 cm <-1 >, and the peak intensity of the second characteristic peak is M2; a third characteristic peak exists at 925 + / -10 cm <-1 >, the peak intensity of the third characteristic peak is M3, Q is defined as the oxygen protection degree of the silicon-based material, and Q, M1, M2 and M3 have the following relation: Q = M1 / M2 + M1 / M3, 1.5 < = Q < = 4.5, and M2 > M3. The oxygen protection degree Q value of the silicon-based material of the negative electrode material is controlled to be 1.5-4.5, so that side reaction between the negative electrode material and electrolyte can be reduced, a proper amount of oxide can be formed on the surface of the silicon-based material, and the volume expansion of the silicon-based material is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of negative electrode materials and a negative electrode material and a secondary battery. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in electric vehicles and consumer electronics because of their high energy density, excellent output power, long cycle life and low pollution to the environment. In order to further improve the energy density of lithium-ion batteries, the research and development of negative electrode materials, especially silicon negative electrode materials, has become particularly important. However, silicon negative electrode materials undergo significant volume expansion (more than 300%) during the process of lithium insertion and extraction, which may cause the silicon negative electrode materials to be easily pulverized and fall off the current collector during the charging and discharging process. This situation will destroy the electrical contact between the active material and the current collector, resulting in a decrease in electrochemical performance, capacity attenuation and cycle stability, making it difficult to commercialize it. In order to solve the above-mentioned problems of poor conductivity and cycle stability of silicon negative electrode materials, researchers have tried to use carbon-based materials to coat silicon-based materials. However, the existing carbon coating preparation process is quite complicated, and simple carbon coating cannot effectively improve the electrochemical performance of silicon-carbon negative electrode materials.

[0003] Therefore, in order to overcome the problems of large silicon volume expansion, poor cycle performance and poor conductivity in the existing technology, it is urgently necessary to develop a silicon-carbon negative electrode material with good conductivity and long cycle life to meet actual application needs. Summary of the invention

[0004] In order to at least solve one or more of the technical problems mentioned above, the present application proposes solutions for improving the prior art in multiple aspects.

[0005] In a first aspect, the present application relates to a negative electrode material, the negative electrode material comprising a silicon-carbon material, the silicon-carbon material comprising a silicon-based material and a carbon-based material, at least part of the carbon-based material being distributed in the silicon-based material;

[0006] The negative electrode material was tested by Raman spectroscopy. -1 The negative electrode material has a first characteristic peak at 305±10cm -1 The negative electrode material has a second characteristic peak at 925±10cm -1There is a third characteristic peak at the location, the peak intensity of the third characteristic peak is M3, Q is defined as the oxygen protection degree of the silicon-based material, and the following relationship exists between Q of the negative electrode material and M1, M2, and M3: Q=M1 / M2+M1 / M3, 1.5≤Q≤4.5 and M2>M3.

[0007] In some embodiments, the carbon-based material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene.

[0008] In some embodiments, the negative electrode material further includes a coating layer, and the coating layer is disposed on at least a portion of the surface of the silicon-carbon material, and the protection strength H of the coating layer is ≥85%.

[0009] In some embodiments, the coating layer satisfies at least one of the following conditions:

[0010] a. The coating layer comprises at least one of a carbon material, a metal oxide, and a nitride;

[0011] b. The thickness of the coating layer is 0.1nm to 100nm.

[0012] In some embodiments, at least a portion of the carbon-based material is distributed on the surface of the silicon-based material and forms the coating layer.

[0013] In some embodiments, the silicon-based material satisfies at least one of the following conditions:

[0014] a. The silicon-based material comprises primary particles, wherein the average particle size of the primary particles is 1nm-20nm;

[0015] b. The silicon-based material includes primary particles, the primary particles include silicon grains, and the average size of the silicon grains is 0.5nm-10nm.

[0016] In some embodiments, the negative electrode material satisfies at least one of the following conditions:

[0017] a. The negative electrode material has pores, and the average pore size of the pores of the negative electrode material is 0.5nm-50nm;

[0018] b. The negative electrode material has pores, and the porosity of the negative electrode material is 0.5%-15%.

[0019] In some embodiments, the negative electrode material satisfies at least one of the following conditions:

[0020] a. The median particle size of the negative electrode material is 0.2 μm-18 μm;

[0021] b. The specific surface area of ​​the negative electrode material is 0.8m2 / g-25m 2 / g;

[0022] c. The powder compaction density of the negative electrode material is 0.8g / cm 3 -1.5g / cm 3 ;

[0023] In some embodiments, the negative electrode material satisfies at least one of the following conditions:

[0024] a. Calculated as a percentage by mass, based on the mass of the negative electrode material, the mass content of carbon in the negative electrode material is 15%-65%;

[0025] b. Calculated as a percentage by mass, based on the mass of the negative electrode material, the mass content of oxygen in the negative electrode material is ≤10%.

[0026] In a second aspect, the present application provides a secondary battery comprising the negative electrode material described in the first aspect.

[0027] The secondary battery provided in the second aspect of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion.

[0028] The advantages of the present application will be partially explained in the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] By reading the detailed description below with reference to the accompanying drawings, the above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0030] Figure 1 The Raman test spectrum of the negative electrode material in Example 1 is shown;

[0031] Figure 2 A scanning electron microscope photograph of the negative electrode material in Example 1 is shown;

[0032] Figure 3 shows the XRD pattern of the negative electrode material in Example 1;

[0033] Figure 4 The cycle performance curve of the negative electrode material in Example 1 is shown, wherein the charge and discharge current is 1000 mA / g. DETAILED DESCRIPTION

[0034] The technical solution of the present application will be described clearly and completely below in conjunction with the specific implementation methods of the present application and the related drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0035] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present application indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.

[0036] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. As used in this application specification and claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms. It should also be further understood that the term "and / or" used in this application specification and claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.

[0037] As used in this specification and claims, the term "if" may be interpreted as "when" or "upon" or "in response to determining" or "in response to detecting," depending on the context. Similarly, the phrase "if it is determined" or "if [described condition or event] is detected" may be interpreted as meaning "upon determination" or "in response to determining" or "upon detection of [described condition or event]" or "in response to detecting [described condition or event]," depending on the context.

[0038] The specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the examples of the present application are all obtained from conventional commercial channels.

[0039] An embodiment of the present application provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), comprising a housing, an electrode assembly, and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing.

[0040] The outer shell can be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery can also be a steel shell battery, an aluminum shell battery, etc.

[0041] The secondary battery includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly may be a laminated structure, which is formed by alternately stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence. In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0042] Positive electrode

[0043] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode active layer contains a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and de-embed metal ions. In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, and the like. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).

[0044] Negative plate

[0045] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The negative electrode active material layer includes a negative electrode material.

[0046] During battery operation, that is, when the battery is in a discharge state, the metal ions (such as lithium ions) in the negative electrode are released from the lattice of the negative electrode material, pass through the isolation membrane through the electrolyte / electrolyte, and are embedded in the lattice of the positive electrode material.

[0047] Conversely, when the battery is charged by applying an external circuit, the oxidation of the positive electrode material causes the metal ions (such as lithium ions) in the positive electrode to escape from the lattice of the positive electrode material, pass through the isolation membrane through the electrolyte / electrolyte, and move to the negative electrode; at the same time, the negative electrode material undergoes a reduction reaction, causing the metal ions to be embedded in the lattice of the negative electrode material.

[0048] As metal ions move back and forth between the positive and negative electrodes, the battery can be discharged and charged thousands of times.

[0049] The performance of negative electrode materials including silicon-based materials and carbon-based materials is mainly affected by the related properties of carbon-based materials and silicon-based materials. There is interference and synergy between silicon-based materials and carbon-based materials. Only by giving full play to the positive synergy between silicon-based materials and carbon-based materials as much as possible and suppressing their negative interference, can the negative electrode materials including silicon-based materials and carbon-based materials exert good electrochemical performance.

[0050] The present application provides a negative electrode material, wherein the negative electrode material includes a silicon-carbon material, wherein the silicon-carbon material includes a silicon-based material and a carbon-based material, wherein the carbon-based material is distributed in the silicon-based material. The negative electrode material is tested by Raman spectroscopy. -1 The first characteristic peak has a peak intensity of M1; the negative electrode material has a peak intensity of M1 at 305±10cm -1 There is a second characteristic peak at 925±10cm -1 There is a third characteristic peak at the location, the peak intensity of the third characteristic peak is M3, Q is defined as the oxygen protection degree of the silicon-based material, and the following relationship exists between Q of the negative electrode material and M1, M2, and M3: Q=M1 / M2+M1 / M3, 1.5≤Q≤4.5 and M2>M3.

[0051] In the above scheme, the first characteristic peak (515±10cm -1 ) can be used to characterize the resonance vibration peak between Si-Si atoms in crystalline silicon. Its peak intensity and shape can reflect the crystal structure and impurity content of silicon. When the first characteristic peak deviates, it can reflect the stress distribution on the surface of Si single crystal. Specifically, if there is stress in the object, some stress-sensitive spectral bands will move and deform. Within the elastic range, the change in Raman peak frequency shift is proportional to the stress. When subjected to compressive stress, the spectral band shifts toward the high frequency direction. On the contrary, when subjected to tensile stress, the spectral band shifts toward the low frequency direction. The second characteristic peak (305±10cm -1 ) is used to characterize the Si-O-Si vibration peak of stable silicon oxide, representing the structure and quality of crystalline silicon oxide in the negative electrode material. The third characteristic peak (925±10cm -1) is used to characterize the Si-O vibration peak of amorphous silicon oxide, representing the thickness and content of the unstable silicon oxide layer on the surface of silicon particles in the negative electrode material. Controlling the peak intensity of the second characteristic peak intensity M2 to be higher than the peak intensity of the third characteristic peak intensity M3 can reduce the activity of oxygen elements in silicon-based materials, reduce the side reactions caused by the contact between silicon oxide and electrolyte in the negative electrode material, form irreversible lithium silicate, and improve the first coulomb efficiency of the negative electrode material. At the same time, the oxygen protection degree Q value of the silicon-based material is controlled between 1.5 and 4.5, that is, the degree of oxidation on the surface of the silicon-based material particles is adjusted and controlled within a reasonable range, which can not only reduce the occurrence of side reactions between the negative electrode material and the electrolyte, but also form an appropriate amount of oxide on the surface of the silicon-based material as a rigid protective layer, alleviate the volume expansion of the silicon-based material, and thus improve the cycle performance of the battery prepared with the negative electrode material. When the Q value is less than 1.5, the content of the oxide layer on the surface of the silicon-based material is relatively high, resulting in a decrease in the specific capacity of the battery prepared with the negative electrode material, a decrease in the first efficiency, and an inability to meet the application requirements. When the Q value is greater than 4.5, the oxide layer on the surface of the silicon-based material is relatively thin, which cannot effectively reduce the side reactions caused by the contact between the silicon-based material and the electrolyte, and the ability to alleviate the volume expansion of the silicon-based material is reduced, resulting in a poor cycle life of the battery prepared with the negative electrode material.

[0052] In some embodiments, the carbon-based material may include at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene. The carbon-based material can be selected from the above materials to form a conductive network with the silicon-based material.

[0053] Reasonable design of carbon-based raw materials for negative electrode materials can effectively inhibit the volume expansion of negative electrode materials and reduce the structural damage of negative electrode materials during the cycle process; it can also enhance the mechanical strength and compressive resistance of negative electrode materials.

[0054] In some embodiments, the negative electrode material further includes a coating layer, which is disposed on at least a portion of the surface of the silicon-carbon material, and the protection strength H of the coating layer is ≥85%.

[0055] In some embodiments, the test method of the protection strength H includes: soaking m1g of negative electrode material in a 20% concentration hydrofluoric acid solution, mechanically stirring for 2 hours, cleaning the residual hydrofluoric acid in the material, and then vacuum drying at 60 degrees to obtain m2g of material, H = m2 / m1×100%, and H is defined as the protection strength of the coating layer. More preferably, the protection strength H of the coating layer of the negative electrode material is ≥90%.

[0056] The coating uniformity and density of the coating layer on the silicon-based material play a vital role in the performance of the silicon-based material. The poor integrity and density of the coating layer will not only cause the silicon-based material to come into direct contact with the electrolyte, resulting in serious side reactions, leading to a decrease in the specific capacity of the entire negative electrode material, a lower initial efficiency, and inability to be used; at the same time, the volume expansion of the silicon-based material cannot be effectively alleviated due to the reduction in the mechanical strength of the coating layer, resulting in poor cycle performance of the battery prepared with the negative electrode material. The negative electrode material provided in the present application reduces the side reactions between the negative electrode material and the electrolyte and improves the electrochemical performance of the negative electrode material by controlling the ratio range of the Raman characteristic peak of the negative electrode material and improving the protective strength of the coating layer in the negative electrode material.

[0057] In some embodiments, the coating layer includes at least one of a carbon material, a metal oxide layer, and a nitride layer.

[0058] In some embodiments, the coating layer may include a carbon material, and the carbon material may be selected from at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, graphene, soft carbon, hard carbon, and the like.

[0059] In some embodiments, at least part of the carbon-based material is distributed on the surface of the silicon-based material and forms the coating layer. The carbon-based material and the coating layer are the same material, which can simplify the preparation process of the negative electrode material.

[0060] In some embodiments, the coating layer may include a metal oxide layer, and the material of the metal oxide layer may include at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0061] In some embodiments, the coating layer may include a nitride layer, and the material of the nitride layer may include at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride.

[0062] In some embodiments, the thickness of the coating layer may be 0.1 nm to 100 nm. For example, the thickness of the coating layer may be 0.1 nm, 5 nm, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, or any value within the range formed by any two of the above values. The coating layer may reduce the solubility of the negative electrode material, thereby reducing the amount of gas produced by the reaction of the dissolved active substance with the electrolyte. Controlling the thickness of the coating layer within the above range is beneficial to maintaining the stability of the particle structure of the negative electrode material during the cycle, and can reduce the exposed active substance on the surface of the negative electrode material. Further, the thickness of the coating layer may be 1 nm to 50 nm, and further, the thickness of the coating layer may be 1 nm to 20 nm, which is beneficial to the rapid and reversible deintercalation of lithium ions.

[0063] In some embodiments, the coating layer may be a single-layer coating layer formed of the above-mentioned single material, or a coating layer formed by a combination of the above-mentioned multiple materials, or a multi-layer coating layer formed of a single material, or a multi-layer coating layer formed of multiple materials, etc. The layer structure of the coating layer can be selected according to actual needs. It can be understood that when the coating layer is a multi-layer coating structure, the density is higher.

[0064] In some embodiments, the silicon-based material includes primary particles, and the average particle size of the primary particles is 1nm-20nm. The average particle size of the primary particles of the silicon-based material can be 1nm, 2nm, 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, or any value within the range formed by any two of the above values, which is not limited here. Controlling the average particle size of the primary particles in the silicon-based material between 1nm and 20nm can adjust the specific surface area and electron transmission path of the negative electrode material, which is beneficial to improving the electrochemical performance of the negative electrode material.

[0065] In some embodiments, the silicon-based material includes primary particles, the primary particles include silicon grains, and the average size of the silicon grains is 0.5nm-10nm. The average size of the silicon grains can be 0.5nm, 0.8nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 8nm, 10nm, or any value within the range of any two of the above values, which is not limited here. Smaller nanoscale silicon grain sizes usually have higher specific surface areas, which are beneficial to charge transfer and ion diffusion of negative electrode materials, and inhibit volume expansion, thereby improving the electrochemical performance, stability and cycle life of negative electrode materials. Furthermore, the average grain size of the silicon-based material can be 2nm to 10nm.

[0066] In the application, the expression "primary particle" refers to the primary structure of a single particle, and the expression "secondary particle" refers to an aggregate of primary particles aggregated by physical or chemical bonding between primary particles, i.e., a secondary structure, without intentionally performing an aggregation or combination process of primary particles constituting secondary particles. Primary particles generally include single crystals and polycrystals. A grain generally refers specifically to a single crystal.

[0067] In some embodiments, the median particle size of the negative electrode material is 0.2μm-18μm. The median particle size of the negative electrode material can be 0.2μm, 0.5μm, 1μm, 2μm, 4μm, 5μm, 8μm, 10μm, 15μm, 18μm or any value within the range formed by any two of the above values, and is not limited here. The median particle size of the negative electrode material directly affects the specific surface area and electron transfer path of the negative electrode material. A smaller particle size usually means a larger specific surface area, which is conducive to the electrochemical reaction and the rapid charge transfer, thereby improving the power density and energy density of the battery; a smaller particle size can reduce the volume change of the material during the lithium ion insertion / extraction cycle, which helps to reduce the stress and deformation of the structure, thereby extending the cycle life of the battery. Further, the median particle size of the negative electrode material can be 1μm to 10μm.

[0068] In some embodiments, the specific surface area of ​​the negative electrode material is 0.8 m 2 / g-25m 2 / g. The specific surface area of ​​the negative electrode material can be 0.8m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g or any value within the range formed by any two of the above values, which is not limited here. Within the above range, it is beneficial to the electrochemical reaction of the battery prepared by the negative electrode material and the rapid charge transfer, thereby improving the electrochemical performance of the negative electrode material. Further, the specific surface area of ​​the negative electrode material can be 2m 2 / g~10m 2 / g.

[0069] In some embodiments, the powder compaction density of the negative electrode material is 0.8 g / cm 3 -1.5g / cm 3 The compacted density of the powder of the negative electrode material can be 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3Or any value within the range formed by any two of the above values, which is not limited here. Within the above compaction density range, the negative electrode material has a suitable charge transfer rate and electrolyte contact area, and also has suitable good structural stability. Further, the powder compaction density of the negative electrode material can be 1g / cm 3 ~1.2g / cm 3 . .

[0070] In some embodiments, the mass content of carbon in the negative electrode material is 15%-65% based on the mass of the negative electrode material, calculated as a percentage by mass. The mass content of carbon in the negative electrode material may be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or any value within the range of any two of the above values, without limitation. Within the above range, by adjusting the carbon content, the electrochemical performance and structural stability of the negative electrode material can be optimized. Furthermore, the carbon content of the negative electrode material may be 10% to 60%.

[0071] In some embodiments, the mass content of oxygen in the negative electrode material is ≤10% based on the mass of the negative electrode material, calculated as a mass percentage. The mass content of oxygen in the negative electrode material may be 1%, 2%, 3%, 4%, 5%, 6%, 8%, or any value within the range formed by any two of the above values.

[0072] In some embodiments, the negative electrode material has pores, and the average pore size of the pores of the negative electrode material is 0.5nm-50nm. The average diameter of the pores can be 0.5nm, 1nm, 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 40nm, 50nm or any value within the range formed by any two of the above values. If the average pore size of the negative electrode material is too large, the electrolyte will easily penetrate into the particles of the negative electrode material during the charge and discharge process of the battery prepared with the negative electrode material, resulting in an increase in side reactions between the negative electrode material and the electrolyte. Moreover, the macropores are the locations where stress is concentrated inside the negative electrode material. The average pore size of the pores of the negative electrode material is too large, which makes it easy for the negative electrode material particles to break and pulverize during the lithium extraction / insertion process, resulting in rapid decay of the cycle performance of the battery prepared with the negative electrode material.

[0073] In some embodiments, the negative electrode material has pores, and the porosity of the negative electrode material is 0.5%-15%. The porosity in the negative electrode material can be 0.5%, 1%, 2%, 3%, 5%, 8%, 10%, 15% or any value within the range of any two of the above values. If the porosity is too large (greater than 15%), the structure of the negative electrode material will be too loose, while if the porosity is too small (less than 0.5%), the negative electrode material will not be able to effectively alleviate the volume expansion of the silicon material and will be broken and pulverized. The battery prepared by the negative electrode material will cause a significant change in volume and capacity decay during the cycle due to the loose structure of the negative electrode material or the pulverization of the particles. Controlling the porosity within the range of 0.5%-15% can effectively extend the service life and cycle stability of the battery prepared by the negative electrode material. Limiting the range of porosity can also adjust the specific surface area and ion diffusion path of the negative electrode material, which is conducive to improving the electron transfer rate and ion diffusion rate of the negative electrode material, thereby improving the charge and discharge efficiency of the battery prepared by the negative electrode material.

[0074] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode material, the method comprising the following steps:

[0075] Step S1, subjecting silicon monoxide raw material to a high-temperature heat treatment to obtain a first product.

[0076] Specifically, a silicon monoxide raw material is placed in a reaction device (such as an atmosphere furnace), and a high-temperature heat treatment is performed under a protective atmosphere to obtain a first product. The main purpose of performing a high-temperature heat treatment on the first material is to pretreat the silicon monoxide raw material, promote the pyrolysis and crystallization process of silicon monoxide, stabilize the structure of the first product, prepare for subsequent chemical reactions and compounding steps, and ensure that the first product has a certain crystal structure and chemical activity.

[0077] In some embodiments, the median particle size D50 of the silicon monoxide raw material is 0.1 μm to 18 μm. Exemplarily, it can be 0.1 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm or 18 μm, etc. Within the above-defined range, it helps to ensure the uniformity and consistency of the silicon monoxide raw material during heat treatment and chemical reaction. At the same time, a smaller particle size helps to improve the specific capacity of the battery, reduce the volume expansion of the negative electrode material, etc. Further, the median particle size D50 of the silicon monoxide raw material can be 2 μm to 15 μm. The particle size test method of the above silicon monoxide raw material can be tested by Malvern laser particle size analyzer (Mastersizer 3000), and the volume reference cumulative particle size distribution of the particle size distribution determination is measured by laser diffraction method. D50 represents the particle size corresponding to the cumulative particle size distribution percentage reaching 50%.

[0078] In some embodiments, the primary sintering is performed at a heating rate of 1°C / min to 20°C / min to 550°C to 1250°C and kept warm for 3h to 12h. Exemplarily, it can be 550°C, 600°C, 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1250°C, etc. Of course, it can also be other values ​​within the above range, and the present application does not limit it here. Through appropriate heating rate, sintering temperature and holding time, it is helpful to pre-treat the silicon monoxide raw material to form a certain crystal structure, which provides a basis for the subsequent reaction with the metal reducing agent.

[0079] In some embodiments, the protective atmosphere of the high-temperature heat treatment is at least one of argon, nitrogen, and helium.

[0080] Step S2, mixing the first product and the metal reducing agent in proportion, and performing a secondary sintering treatment to obtain a second product.

[0081] Specifically, the first product and the metal reducing agent are mixed uniformly in a certain proportion, and then placed in a reaction device (e.g., a reactor), and a protective gas is introduced to replace the air, and secondary sintering is performed, and the second product is obtained after cooling. The addition of the metal reducing agent is intended to react chemically with the first product. For example, the first product formed by using silicon monoxide as the first material reacts with the metal reducing agent to form a silicon-metal compound or a silicon-metal alloy. The secondary sintering process also helps to ensure the uniformity and stability of the negative electrode material.

[0082] In some embodiments, the metal reducing agent may include at least one of magnesium powder, aluminum powder, and lithium powder. The above metal reducing agents all have good reducibility, which is beneficial to the reduction and alloying of the first product; at the same time, the introduction of the metal reducing agent also helps to improve the conductivity, ion diffusion performance and cycle stability of the negative electrode material.

[0083] In some embodiments, the mass ratio of the first product to the metal reducing agent is 1:(0.2-1.2), and can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, and can further be 1:(0.2-0.8). A suitable ratio can achieve a better reaction between the first product and the metal reducing agent.

[0084] In some embodiments, the secondary sintering is carried out by heating the temperature at a rate of 1°C / min to 20°C / min to a secondary sintering temperature of 250°C to 850°C and keeping the temperature for 1h to 24h, which may be 250°C, 350°C, 400°C, 500°C, 600°C, 700°C, 800°C, or 850°C, etc., wherein the secondary sintering temperature may further be 300°C to 600°C, and of course may be other values ​​within the above range, which are not limited in this application. By appropriate heating rate, sintering temperature and holding time, it is possible to ensure that the reaction reaches a sufficient temperature and time, which can promote the reaction of the first product with the metal reducing agent, and improve the crystallinity and stability of the crystal structure of the second product.

[0085] Step S3, purifying the second product by etching with an etching solution to remove by-products and obtain a silicon-based material precursor.

[0086] It can be understood that the primary particles with pores, i.e., the silicon-based material precursor, are obtained through etching treatment, which facilitates the subsequent carbon-based material to enter the pores of the primary particles. Compared with the primary particles without pores, the primary particles of this embodiment can alleviate the volume expansion of the silicon-based material itself. The negative electrode material obtained by the preparation method of the embodiment of the present application has better expansion performance.

[0087] In some embodiments, the mass ratio of the second product to the etching solution is 1:(5-20), and can specifically be, for example, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20 or a range consisting of any two of these values, and of course can also be other values ​​within the above range, which is not limited here.

[0088] In some embodiments, the etching solution includes at least one of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and ammonium bifluoride.

[0089] In some embodiments, the molar concentration of the etching solution is 1-10 mol / L.

[0090] In some embodiments, the etching reaction time is 0.5 h to 10 h, and specifically can be, for example, 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 9 h, 10 h or a range consisting of any two of these values, which is not limited here.

[0091] In some embodiments, the temperature of the etching reaction is ≤30°C, and can be, for example, 30°C, 28°C, 25°C, 20°C, 15°C, or a range consisting of any two of these values. Of course, it can also be other values ​​within the above range, which is not limited here.

[0092] In some embodiments, the method further comprises washing and drying the etching reaction product, and the drying temperature is ≤85°C.

[0093] In some embodiments, the mass content of oxygen in the silicon-based material precursor is less than 6%. Specifically, it can be, for example, 5.9%, 4.9%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1% or a range consisting of any two of these values, and of course, it can also be other values ​​within the above range, which is not limited here.

[0094] In some embodiments, the mass content of water in the silicon-based material precursor is less than 1.5%, and can be, for example, 1.49%, 0.99%, 0.9%, 0.8%, 0.6%, 0.5%, 0.4%, 0.3%, 0.2%, 0.1% or a range consisting of any two of these values. Of course, it can also be other values ​​within the above range, which is not limited here.

[0095] In some embodiments, the median particle size of the silicon-based material precursor is 0.1 μm-15 μm.

[0096] In some embodiments, the silicon grain size of the silicon-based material precursor is 0.2 nm to 16 nm.

[0097] In some embodiments, the porosity of the silicon-based material precursor is 25%-65%.

[0098] In some embodiments, the specific surface area of ​​the silicon-based material precursor is 250 m 2 / g-650m 2 / g.

[0099] In some embodiments, the average pore volume of the silicon-based material precursor is 0.24 cm 3 / g-0.66cm 3 / g.

[0100] Step S4, depositing carbon-based materials inside the silicon-based material precursor by pulsed chemical vapor deposition and reserving holes to obtain a silicon-carbon composite material.

[0101] In some embodiments, the pulsed chemical vapor deposition method is used to deposit carbon-based materials inside a silicon-based material precursor and reserve holes. The specific steps include: the silicon-based material precursor is placed in a reaction furnace, the air therein is replaced with an inert gas, and after being heated to a certain temperature, a gaseous carbon source is introduced by pulse air intake, and the internal carbon-based material deposition rate and efficiency are changed by controlling the amount of gas entering in a short time, and then the carbon source is continuously introduced to continue to deposit carbon inside. After a certain period of insulation, the carbon source undergoes a thermal cracking reaction, so that the carbon-based material is deposited inside the silicon-based material precursor, and holes are reserved therein to obtain a silicon-carbon composite material.

[0102] Wherein, the heating rate of the gas phase carbon deposition in the pulse chemical vapor deposition is 1°C / min-30°C / min. The reaction temperature of the gas phase carbon deposition in the pulse chemical vapor deposition is 200°C-1050°C. The holding time of the gas phase carbon deposition in the pulse chemical vapor deposition is 1h-24h. The gas phase carbon source in the pulse chemical vapor deposition includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole and acetonitrile. The flow rate of the gas phase carbon source in the pulse chemical vapor deposition is 0.1L / min-10L / min. The pulse frequency is 10hz-500hz. The pulse duration is 10ms-800ms. The pulse duration is 1h-8h.

[0103] Step S5, performing surface coating treatment on the silicon-carbon composite material using a coating material, wherein the coating material includes at least one of a carbon material, a metal oxide layer, and a nitride.

[0104] In some embodiments, a dense coating layer is coated on the surface of a silicon-carbon composite material by fluidized bed chemical vapor deposition, and the carbon coating layer is used as an example. The specific steps include: placing the silicon-carbon composite material in a vertical fluidized bed device, replacing the air therein with an inert gas, heating it to a certain temperature, introducing an inert gas as a power gas of the material, and making the material in a fluid state. A certain flow of gaseous carbon source is introduced, and after a certain period of heat preservation, the carbon source undergoes a thermal cracking reaction, so that a dense carbon layer is deposited on the surface of the silicon-carbon composite material to obtain a negative electrode material.

[0105] In some embodiments, the inert gas includes one or more of nitrogen, helium, neon, argon, and krypton.

[0106] Wherein, the heating rate of the gas phase carbon deposition in the fluidized bed chemical vapor deposition is 1°C / min-20°C / min. The flow rate of the power gas used for the gas phase carbon deposition in the fluidized bed chemical vapor deposition is 1.5L / min-25L / min. The reaction temperature of the gas phase carbon deposition in the fluidized bed chemical vapor deposition is 600°C-1150°C. The holding time of the gas phase carbon deposition in the fluidized bed chemical vapor deposition is 0.5h-24h. The gas phase carbon source in the fluidized bed chemical vapor deposition includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, and liquefied gas. The flow rate of the gas phase carbon source in the fluidized bed chemical vapor deposition is 0.5L / min-15L / min.

[0107] The metal reducing agent reacts with the first product to reduce the silicon oxide in the first product to silicon element, thereby controlling the intensity of the first characteristic peak; the etching process with the etching solution can remove the oxygen element on the surface of the silicon-based material, control the intensity of the second characteristic peak and the third characteristic peak, and thus adjust the oxygen protection degree of the silicon-based material. In addition, the carbon-based material is deposited inside the silicon-based material precursor by pulsed chemical vapor deposition and holes are reserved, and a dense carbon layer is also wrapped on its surface by fluidized bed chemical vapor deposition, finally forming a negative electrode material.

[0108] By adopting the pulsed air intake method, the carbon deposition rate of the carbon source inside the material can be accurately controlled. A portion of the pores can be reserved while depositing the carbon-based material inside the material, thereby adjusting the porosity of the negative electrode material, which is beneficial to alleviate the volume expansion of the silicon-based material. In addition, the surface of the material is further uniformly coated by fluidized bed chemical vapor deposition to form a dense coating layer on the surface of the material, which can effectively reduce the electrolyte from directly penetrating into the particles of the negative electrode material through the pore structure, reduce the side reactions caused by the contact between the electrolyte and the silicon-based material, and improve the cycle performance of the battery prepared by the negative electrode material. Through the synergistic effect of pulsed carbon deposition and coating process, the internal pores of the negative electrode material are reserved and the surface is densely coated, and the protective strength H of the coating layer of the negative electrode material is controlled to be ≥85%, which can not only reduce the expansion rate of the negative electrode material, but also be beneficial to form a stable solid electrolyte film on the surface of the negative electrode material, and also be beneficial to improve the stability of the material, thereby improving the electrochemical performance of the negative electrode material.

[0109] In a third aspect, the present invention provides a secondary battery, wherein the secondary battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.

[0110] The secondary battery provided in the third aspect of the embodiment of the present invention has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion.

[0111] Specific Examples and Comparative Examples

[0112] Example 1

[0113] (1) Putting silicon monoxide raw material into an atmosphere furnace, heating to 950° C. at a heating rate of 3° C. / min under the protection of argon atmosphere, keeping the temperature for 5 hours and then cooling to obtain the first product.

[0114] (2) The first product and metal aluminum powder are mixed evenly in a molar ratio of 1:0.5, and then placed in a reaction furnace. Protective gas is introduced to replace the air, and the mixture is heated to 650°C at a heating rate of 3°C / min. The mixture is kept warm for 4 hours and then cooled to obtain the second product.

[0115] (3) The second product is put into an etching solution for purification. The mass ratio of the second product to the etching solution is 1:5. The concentration of the etching solution is 6 mol / L. The etching solution includes hydrochloric acid and hydrofluoric acid. The etching reaction time is 1.5 h. The temperature of the etching reaction is controlled at 25° C. After washing and drying, a silicon-based material precursor is obtained.

[0116] (4) Place 500 g of silicon-based material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 750 °C at a heating rate of 3 °C / min under the protection of an argon atmosphere. Set the acetylene gas flow rate to 2.5 L / min, and introduce the carbon source into the pulse generator. Set the pulse frequency to 50 Hz, the pulse duration to 200 ms, and the pulse duration to 3 h. After turning off the pulse generator, continue to introduce acetylene gas at a flow rate of 2.5 L / min for 2 h, and cool to obtain a silicon-carbon composite material.

[0117] (5) 1 kg of silicon-carbon composite material was placed in a vertical fluidized bed apparatus, the air therein was replaced with an inert gas, 3 L / min of argon was introduced as a power gas, and after heating to 750 °C at a heating rate of 3 °C / min, 2 L / min of propane was introduced as a carbon source gas. After keeping the temperature for 3 h, the negative electrode material was obtained by cooling.

[0118] The detailed physical and chemical parameters of the negative electrode material in this embodiment are shown in Table 1.

[0119] Figure 1 is the Raman test spectrum of the negative electrode material in this embodiment; Figure 2 This is a scanning electron microscope image of the negative electrode material in this embodiment; Figure 3 is the XRD diagram of the negative electrode material in this embodiment; Figure 4 The cycle performance curve of the battery prepared by the negative electrode material in this embodiment has a charge and discharge current of 1000 mA / g.

[0120] from Figure 1 It can be seen from the Raman spectrum that the negative electrode material has a peak at 516 cm -1 The peak intensity of the first characteristic peak at 3716 is 3716; at 308cm -1 The peak intensity of the second characteristic peak at 925cm -1 The peak intensity of the first characteristic peak at is 2124, and the calculated Q value is 3.35.

[0121] from Figure 2 It can be seen from the scanning electron microscope image that the surface of the prepared silicon-carbon negative electrode material is relatively smooth and there is no cracking.

[0122] from Figure 3It can be seen from the XRD spectrum that the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No. 27-1402), and there is basically no impurity phase. According to the Scherrer formula, the silicon grain size is calculated to be 3.5nm.

[0123] Figure 4 It can be seen that the material has excellent cycle performance, with a capacity retention rate of 83.4% after 50 cycles at a current of 0.25C.

[0124] Example 2

[0125] (1) Putting silicon monoxide raw material into an atmosphere furnace, heating to 970° C. at a heating rate of 3° C. / min under the protection of argon atmosphere, keeping the temperature for 6 hours and then cooling to obtain the first product.

[0126] (2) The first product and metal aluminum powder are mixed evenly in a molar ratio of 1:0.3, and then placed in a reaction furnace. Protective gas is introduced to replace the air, and the mixture is heated to 650°C at a heating rate of 3°C / min. The mixture is kept warm for 4 hours and then cooled to obtain the second product.

[0127] (3) The second product is put into an etching solution for purification. The mass ratio of the second product to the etching solution is 1:10. The concentration of the etching solution is 3 mol / L. The etching reaction time is 2.5 h. The temperature of the etching reaction is controlled at 25° C. After washing and drying, a silicon-based material precursor is obtained.

[0128] (4) Place 500 g of silicon-based material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 700 °C at a heating rate of 3 °C / min under the protection of an argon atmosphere. Set the acetylene gas flow rate to 0.5 L / min, and introduce the carbon source into the pulse generator. Set the pulse frequency to 500 Hz, the pulse duration to 10 ms, and the pulse duration to 8 h. After turning off the pulse generator, continue to introduce acetylene gas at a flow rate of 2.5 L / min for 1 h, and cool to obtain a silicon-carbon composite material.

[0129] (5) 1 kg of silicon-carbon composite material was placed in a vertical fluidized bed apparatus, the air therein was replaced with an inert gas, 4 L / min of argon was introduced as a power gas, and after heating to 650 °C at a heating rate of 5 °C / min, 3 L / min of propane was introduced as a carbon source gas. After keeping the temperature for 4 h, the negative electrode material was obtained by cooling.

[0130] The detailed physical and chemical parameters of the negative electrode material in this embodiment are shown in Table 1.

[0131] Example 3

[0132] (1) Putting silicon monoxide raw material into an atmosphere furnace, heating to 970° C. at a heating rate of 3° C. / min under the protection of argon atmosphere, keeping the temperature for 6 hours and then cooling to obtain the first product.

[0133] (2) The first product and metal aluminum powder are mixed evenly in a molar ratio of 1:0.3, and then placed in a reaction furnace. Protective gas is introduced to replace the air, and the mixture is heated to 650°C at a heating rate of 3°C / min. The mixture is kept warm for 4 hours and then cooled to obtain the second product.

[0134] (3) The second product is put into an etching solution for purification. The mass ratio of the second product to the etching solution is 1:10. The concentration of the etching solution is 8 mol / L. The etching reaction time is 2.5 h. The temperature of the etching reaction is controlled at 25° C. After washing and drying, a silicon-based material precursor is obtained.

[0135] (4) Place 500 g of silicon-based material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 900 °C at a heating rate of 3 °C / min under the protection of an argon atmosphere. Then, set the acetylene gas flow rate to 9.5 L / min, and introduce the carbon source into the pulse generator. Set the pulse frequency to 10 Hz, the pulse duration to 800 ms, and the pulse duration to 4 h. After turning off the pulse, continue to introduce acetylene gas at a flow rate of 1.5 L / min for 2 h, and cool to obtain a silicon-carbon composite material.

[0136] (5) 1 kg of silicon-carbon composite material was placed in a vertical fluidized bed apparatus, the air therein was replaced with an inert gas, 4 L / min of argon was introduced as a power gas, and after heating to 650 °C at a heating rate of 5 °C / min, 3 L / min of propane was introduced as a carbon source gas. After keeping the temperature for 4 h, the negative electrode material was obtained by cooling.

[0137] The detailed physical and chemical parameters of the silicon-carbon negative electrode material in this embodiment are shown in Table 1.

[0138] Example 4

[0139] (1) Putting silicon monoxide raw material into an atmosphere furnace, heating to 750° C. at a heating rate of 3° C. / min under the protection of argon atmosphere, keeping the temperature for 5 hours and then cooling to obtain the first product.

[0140] (2) The first product and metal magnesium powder were mixed evenly in a molar ratio of 1:0.2, and then placed in a reaction furnace. Protective gas was introduced to replace the air. The mixture was heated to 620°C at a heating rate of 3°C / min, kept warm for 5 hours, and then cooled to obtain the second product.

[0141] (3) The second product is put into an etching solution for purification. The mass ratio of the second product to the etching solution is 1:10. The concentration of the etching solution is 10 mol / L. The etching reaction time is 1.5 h. The temperature of the etching reaction is controlled at 25° C. After washing and drying, a silicon-based material precursor is obtained.

[0142] (4) Place 500 g of silicon-based material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 950 °C at a heating rate of 3 °C / min under the protection of an argon atmosphere. Then set the acetylene gas flow rate to 10 L / min, and introduce the carbon source into the pulse generator. Set the pulse frequency to 10 Hz, the pulse duration to 800 ms, and the pulse duration to 8 h. After turning off the pulse generator, continue to introduce acetylene gas at a flow rate of 0.1 L / min for 3 h, and cool to obtain a silicon-carbon composite material.

[0143] (5) 1 kg of silicon-carbon composite material was placed in a vertical fluidized bed apparatus, the air therein was replaced with an inert gas, 4 L / min of argon was introduced as a power gas, and after heating to 600 °C at a heating rate of 5 °C / min, 1 L / min of propane was introduced as a carbon source gas. After keeping the temperature for 2 h, the negative electrode material was obtained by cooling.

[0144] The remaining parameters of the negative electrode material in this embodiment are detailed in Table 1.

[0145] Example 5

[0146] The negative electrode material was prepared in a method substantially the same as that of Example 1, except that the heating temperature in step (1) was 780° C. and the concentration of the etching solution in step (3) was 1 mol / L.

[0147] Example 6

[0148] The negative electrode material was prepared in a method substantially the same as that in Example 1, except that the etching time in step (3) was 3 h.

[0149] Example 7

[0150] The negative electrode material was prepared in substantially the same manner as in Example 1, except that the reaction temperature in step (5) was 850°C.

[0151] Example 8

[0152] The negative electrode material was prepared in a method substantially the same as that of Example 1, except that the concentration of the carbon source in step (5) was 8 L / min.

[0153] Comparative Example 1

[0154] Steps (1), (2), (3) and (5) are basically the same as those in Example 1, and step (4) is a conventional CVD

[0155] (4) 500 g of silicon-based material precursor was placed in a rotary atmosphere furnace, the air therein was replaced with an inert gas, and under the protection of an argon atmosphere, the temperature was heated to 750 °C at a heating rate of 3 °C / min, and the acetylene gas flow rate was set to 2.5 L / min, and acetylene gas was continuously introduced for 5 h, and then cooled to obtain a silicon-carbon composite material.

[0156] The detailed physical and chemical parameters of the negative electrode material in this embodiment are shown in Table 1.

[0157] Comparative Example 2

[0158] Steps (1), (3), (4) and (5) are basically the same as those in Example 1, except that no aluminum powder is added in step (2).

[0159] (2) The first product is placed in a reaction furnace, a protective gas is introduced to replace the air, and the temperature is heated to 650°C at a heating rate of 3°C / min. The temperature is kept at this temperature for 4 hours and then cooled to obtain the second product.

[0160] The detailed physical and chemical parameters of the negative electrode material in this embodiment are shown in Table 1.

[0161] Comparative Example 3

[0162] Steps (1), (4) and (5) are basically the same as those in Example 1. In step (2), an excess amount of metallic magnesium powder is added. In step (3), the mass ratio of the second product to the etching solution is 1:25, the concentration of the etching solution is 11 mol / L, and the etching reaction time is 4.5 h.

[0163] (2) The first product intermediate product and metal magnesium powder are mixed evenly in a molar mass ratio of 1:3, put into a reaction furnace, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.

[0164] (3) The second product is put into an etching solution for purification. The mass ratio of the second product to the etching solution is 1:25. The concentration of the etching solution is 11 mol / L. The etching reaction time is 4.5 h. The temperature of the etching reaction is controlled at 25° C. After washing and drying, a silicon-based material precursor is obtained.

[0165] The detailed physical and chemical parameters of the negative electrode material in this embodiment are shown in Table 1.

[0166] Test method:

[0167] 1) Raman test of negative electrode materials:

[0168] The Raman spectrum was tested using the XPLORA laser confocal Raman spectrometer from HORIBA, Japan, including the Raman peak position, peak intensity, half-peak width, etc. Specifically, the sample was placed on the sample stage of the Raman spectrometer to ensure that the sample was aligned with the laser beam. The test conditions were: 532nm laser was used and the test range was 100cm -1 -3000cm -1 Zero point calibration is performed using standard materials to ensure the precision and accuracy of the spectrum. Laser light is used to excite the sample and the frequency and intensity of the scattered light are measured.

[0169] 2) Test method for specific surface area of ​​negative electrode materials:

[0170] Specific surface area and specific pore volume test method: Using the ASAP2406 surface area and pore size analyzer from Micromeritics, USA, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, a variety of models can be fitted to calculate the specific surface area.

[0171] 3) Test of coating protection strength H:

[0172] A negative electrode material with a mass of m1g was immersed in a 20% concentration hydrofluoric acid solution, and after mechanical stirring for 2 hours, the residual hydrofluoric acid was washed away, and m2g of material was obtained after vacuum drying at 60 degrees. The protective strength of the coating layer in the negative electrode material was calculated to be H=m2 / m1×100%.

[0173] 4) Particle size of negative electrode material:

[0174] The particle size test method refers to GB / T 19077-2016. D50 is measured using a laser particle size analyzer, which has a symmetrical distribution similar to a normal distribution. In its volume reference distribution, the cumulative 50% diameter is D50, and by analogy, the cumulative 90% diameter is D90, and the cumulative 10% diameter is D10. An example of a laser particle size analyzer is the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0175] 5) Testing method of compaction density:

[0176] Using the American CARVER 4350.22 powder compaction density tester, a sample of specified mass m is placed in a mold and a pressure of 1.0T is applied. After maintaining the pressure for 30S, the pressure is removed to test its thickness and the compaction density is calculated.

[0177] 6) Test method for oxygen content and carbon content in negative electrode materials:

[0178] The oxygen content was measured by Fourier transform infrared spectrometer, and the carbon layer content was tested by thermogravimetric analysis.

[0179] 7) SEM test:

[0180] Scanning electron microscopy characterization was performed on a transmission electron microscope with an operating voltage of 200 kV to observe the structure of the negative electrode material and to scale the thickness of the coating layer. For example, the coating layer thickness: the material was sectioned using a FIB-SEM device, 10 particles were randomly selected in the SEM, and the coating layer thickness of each particle was measured 3 times to obtain the average coating layer thickness.

[0181] 8) Test method for average primary particle size:

[0182] The material is sectioned using a FIB-SEM device, the sizes of 20 primary particles are measured in the SEM, and the average value is calculated as the average size of the primary particles.

[0183] 9) Test method for average silicon grain size:

[0184] The XRD spectrum of the sample was measured by X-ray diffractometer, the half-peak width of the sample diffraction peak and the corresponding Bragg angle were obtained by jade software, and the average grain size of nano-silicon was calculated by Scherrer formula D=Kγ / Bcosθ.

[0185] 10) Porosity test method:

[0186] Mercury intrusion porosimetry is a method for calculating porosity by measuring the pressure change of mercury in the pores of a material. This method uses the AutoPore IV 9500 high-performance fully automatic mercury intrusion porosimeter from Micromeritics Instruments to press mercury into the pores of the material, and the porosity and pore distribution can be calculated based on the volume change and pressure change of mercury.

[0187] After the above tests, the negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3 have sample numbers corresponding to S1 to S8 and R1 to R3; the performance parameters of the negative electrode materials are shown in Table 1:

[0188] Table 1

[0189]

[0190]

[0191] 8) Electrochemical test:

[0192] The negative electrode material was mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6) and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare a slurry, which was evenly coated on a copper foil and dried to make a negative electrode sheet. The negative electrode sheet was assembled into a button cell in an argon atmosphere glove box. The separator used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.

[0193] The above 12 groups of batteries were tested for discharge specific capacity on a Blue Power CT2001A battery testing system. The ratio of the amount of electricity discharged in one hour to the battery capacity is the discharge specific capacity.

[0194] The above 12 groups of batteries were subjected to the first coulombic efficiency test on the Blue Power CT2001A battery testing system, with the charge and discharge current being 0.05C, and the first coulombic efficiency was measured.

[0195] The above 12 groups of batteries were tested for 50 cycles on the Blue Power CT2001A battery testing system with a charge and discharge current of 0.25C. After 50 cycles, the battery capacity and capacity retention rate after the cycle were calculated.

[0196] Among them, the capacity retention rate after 50 cycles at 0.25C = 50th cycle discharge capacity / first cycle discharge capacity * 100%. The results are shown in Table 2.

[0197] Table 2 Parameter performance comparison of each battery

[0198]

[0199] According to the results shown in Tables 1-2, in order to ensure the relationship between the balanced specific capacity and cycle life of the negative electrode material, the degree of oxidation on the surface of the silicon particles is adjusted through synthetic process control, so that the oxygen protection degree Q value of the silicon-based material is between 1.5-4.5. Within this reasonable range, it can not only reduce the occurrence of side reactions between the negative electrode material and the electrolyte, but also form an appropriate amount of oxide on the surface of the silicon-based material as a rigid protective layer, alleviate the volume expansion of the silicon-based material, and thus improve the cycle performance of the battery prepared with the negative electrode material. The present application controls the protective strength H ≥ 85% of the coating layer of the negative electrode material through the synergistic effect of the deposition process of the carbon-based material and the coating process, which can reduce the infiltration of active substances in the negative electrode material, such as silicon-based materials, with the electrolyte, improve the capacity and first effect of the battery prepared with the negative electrode material, and at the same time alleviate the volume expansion of the silicon-based material, and improve the cycle and rate performance of the battery prepared with the negative electrode material.

[0200] Compared with Example 1, Example 2 reduces the amount of metal reducing agent used in the preparation process, and the intensity of the first characteristic peak of the obtained negative electrode material is reduced, so that the oxygen protection degree Q of the silicon-based material is reduced, and the cycle retention rate of the composite material in Example 2 is reduced, and the volume expansion is increased. Compared with Example 1, in the vertical fluidized bed carbon coating process, Example 4 reduces the coating temperature, resulting in a reduced coating effect and a reduced carbon content in the negative electrode material, that is, the thickness of the coating layer in the negative electrode material is thin, the mass of the coating layer accounts for a small proportion, and the protective strength of the coating layer is reduced, resulting in a reduced first effect of the battery prepared from the negative electrode material.

[0201] Compared with Example 2, in Example 3, the concentration of the etching solution is increased during the preparation process, resulting in a significant decrease in the intensity of the third characteristic peak, a thinner oxide layer on the surface of the silicon-based material, and ultimately an increase in the oxygen protection degree Q of the silicon-based material of the negative electrode material in Example 3, which ultimately leads to an increase in the specific capacity of the negative electrode material in Example 3 and an improvement in the first effect.

[0202] Compared with Example 1, Example 5 reduces the concentration of the etching solution. On the one hand, the oxide by-products produced in the reduction process cannot be effectively removed, resulting in a decrease in the intensity of the first characteristic peak. On the other hand, the reduced concentration preferentially etches the amorphous oxide on the surface of the silicon-based material, resulting in a decrease in the intensity of the second characteristic peak. Ultimately, the oxygen protection degree Q of the silicon-based material is reduced, and the cycle retention rate and first effect are reduced.

[0203] Compared with Example 1, Example 6 extends the etching time of the etching solution, resulting in an increase in the porosity of the negative electrode material. Under the same carbon deposition conditions, the carbon coating effect is poor, resulting in a decrease in the protection strength of the coating layer, resulting in degradation of the material's cycle performance. However, since sufficient pores are reserved inside the negative electrode material, the volume expansion of the silicon-based material in the negative electrode material can be effectively alleviated, and thus the volume expansion rate of the negative electrode material is reduced.

[0204] Compared with Example 1, in Example 7 and Example 8, the reaction temperature and carbon source concentration in step (5) were respectively increased during the preparation process, resulting in a significant improvement in carbon coating efficiency, an increase in carbon content, an increase in density, and an increase in the protective strength H of the coating layer, but a decrease in the specific capacity of the negative electrode material. As the temperature and concentration of the coating process increase, the carbon source concentration increases, and the carbon source cracking is an exothermic reaction, the increase in carbon source concentration leads to an increase in local temperature, which also leads to an increase in the size of silicon grains, resulting in deterioration of cycle performance and expansion performance.

[0205] Compared with Example 1, in Comparative Example 1, traditional CVD is used instead of pulsed chemical vapor deposition in the preparation process, resulting in low filling efficiency of carbon-based materials in silicon-based materials, increased porosity and specific surface area of ​​the obtained negative electrode material, and reduced protection strength H of the coating layer under the same coating conditions. The cycle performance and expansion performance of the battery prepared with the negative electrode material deteriorate, and the first efficiency is significantly reduced.

[0206] Compared with Example 1, in Comparative Example 2, no metal aluminum powder is added in step (2) during the preparation process, resulting in a significant decrease in the intensity of the first characteristic peak and an increase in the intensity of the third characteristic peak, which ultimately results in the oxygen protection degree Q of the silicon-based material being less than 1.5, resulting in a decrease in the specific capacity of the battery prepared with the negative electrode material, which cannot meet the application requirements.

[0207] Compared with Example 1, in Comparative Example 3, the amount of metal reducing agent is excessive and the content and concentration of the etching solution are significantly increased during the preparation process, which ultimately leads to the oxygen protection degree Q of the silicon-based material being greater than 4.5, and the specific capacity and first efficiency of the obtained negative electrode material are significantly increased. However, the surface oxide layer of the silicon-based material is relatively thin, which cannot effectively reduce the side reactions generated by the contact between the silicon-based material and the electrolyte, and cannot effectively alleviate the volume expansion of the silicon-based material, resulting in a poor cycle life of the battery prepared with the negative electrode material.

[0208] In summary, the negative electrode material of the present application has the advantages of low expansion and good cycle stability.

[0209] The embodiments of the present application are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and its core idea of ​​the present application. At the same time, changes or deformations made by those skilled in the art based on the ideas of the present application, the specific implementation methods and the scope of application of the present application, all belong to the scope of protection of the present application. In summary, the content of this specification should not be construed as a limitation on the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes a silicon-carbon material, the silicon-carbon material includes a silicon-based material and a carbon-based material, and at least part of the carbon-based material is distributed in the silicon-based material; The negative electrode material was tested by Raman spectroscopy. -1 The negative electrode material has a first characteristic peak at 305±10cm -1 The negative electrode material has a second characteristic peak at 925±10cm -1 There is a third characteristic peak at the location, the peak intensity of the third characteristic peak is M3, Q is defined as the oxygen protection degree of the silicon-based material, and the following relationship exists between Q of the negative electrode material and M1, M2, and M3: Q=M1 / M2+M1 / M3, 1.5≤Q≤4.5 and M2>M3.

2. The negative electrode material according to claim 1, characterized in that The carbon-based material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers and graphene.

3. The negative electrode material according to claim 1, characterized in that The negative electrode material further includes a coating layer, which is disposed on at least a portion of the surface of the silicon-carbon material, and the protection strength H of the coating layer is ≥85%.

4. The negative electrode material according to claim 3, characterized in that The coating layer satisfies at least one of the following conditions: a. The coating layer comprises at least one of a carbon material, a metal oxide, and a nitride; b. The thickness of the coating layer is 0.1nm to 100nm.

5. The negative electrode material according to claim 1, characterized in that The silicon-based material satisfies at least one of the following conditions: a. The silicon-based material comprises primary particles, wherein the average particle size of the primary particles is 1nm-20nm; b. The silicon-based material includes primary particles, the primary particles include silicon grains, and the average size of the silicon grains is 0.5nm-10nm.

6. The negative electrode material according to claim 3, characterized in that At least part of the carbon-based material is distributed on the surface of the silicon-based material and forms the coating layer.

7. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: a. The negative electrode material has pores, and the average pore size of the pores of the negative electrode material is 0.5nm-50nm; b. The negative electrode material has pores, and the porosity of the negative electrode material is 0.5%-15%.

8. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: a. The median particle size of the negative electrode material is 0.2 μm-18 μm; b. The specific surface area of ​​the negative electrode material is 0.8m 2 / g-25m 2 / g; c. The powder compaction density of the negative electrode material is 0.8g / cm 3 -1.5g / cm 3 .

9. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: a. Calculated as a percentage by mass, based on the mass of the negative electrode material, the mass content of carbon in the negative electrode material is 15%-65%; b. Calculated as a percentage by mass, based on the mass of the negative electrode material, the mass content of oxygen in the negative electrode material is ≤10%.

10. A secondary battery, characterized in that: The negative electrode material comprises the negative electrode material as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Negative electrode material and secondary battery

    EP4822770A1

  • Negative electrode material and secondary battery

    WO2026012009A1

  • Negative electrode material

    WO2026046441A1

  • Negative electrode material and secondary battery

    WO2026208339A1